The relationship between entrepreneurial orientation and performance of SMEs in Indonesia - Tambunan, Damelina Basauli; Hashim, Norashidah (American Scientific Publishers, 2018)
The purpose of this research is to find out the relationship between entrepreneurial orientation and performance of small medium enterprises (SMEs) in East Java Indonesia. A total of 381 small medium enterprises in the East Java province of Indonesia are used as research respondents. These respondents were selected using proportional cluster random method to ensure that all of the predetermined areas in East Java were proportionally represented. Confirmatory Factor Analysis (CFA) is used to test the validity of the research variables, whereas Composite (Construct) Reliability is used to test the reliability of the variables. After all variables were declared as valid and reliable, the following step was to perform a multivariate analysis which involved normality, singularity, and outlier tests. After all the multivariate assumptions were fulfilled, a structural model testing was performed using the covarian-based structural model of AMOS. The model was tested using covarian-based Structural Equation Model. The result of this research suggests that entrepreneurial orientation has a positive and significant influence on performance of SMEs. This study provides new empirical evidence of entrepreneurial orientation and the influence on performance of small medium enterprises in Indonesia, which involve big amount of data (381) and use of AMOS. Therefore, some practical contributions are provided and several recommendation have been proposed for further researches.